PENGEMBANGAN MEDIA QUINOSS DALAM MENINGKATKAN KEMAMPUAN COMPITATIONAL THINKING ANAK USIA DINI - Monik Dwi Pramudita, Adis; Matheos Lasarus Malaikosa, Yes; Agustin Ningrum, Mallevi; Gowinda Luh Safitri, Dhian (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to develop and examine the effectiveness of QUINOSS (Quiet Book Unplugged Coding Solar System) as a learning medium to improve computational thinking skills in early childhood. The research employed a Research and Development approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects were 40 children aged 5–6 years from five kindergartens. Data were collected through observation sheets of children’s computational thinking abilities, teacher practicality questionnaires, and expert validation instruments. The results showed that the QUINOSS media was highly valid based on expert evaluations of media and content, with excellent validity criteria. The practicality test indicated that the media was very practical with a percentage score of 85%. Furthermore, effectiveness testing using one-way ANOVA demonstrated that QUINOSS significantly improved children’s computational thinking abilities, including decomposition, pattern recognition, abstraction, and algorithmic thinking. These findings indicate that QUINOSS is an effective and applicable unplugged coding learning medium for early childhood education, particularly in settings with limited access to digital technology.